Analysis of inpatients’ characteristics and spatio-temporal distribution of liver cancer incidence in Wuwei, Gansu Province, from 1995 to 2016: A long-term span retrospective study - Zhang, Yang (Medicine (Baltimore), 2020)
This long-term span retrospective study aimed to determine the incidence and spatial-temporal trends of liver cancer in Wuwei city from 1995 to 2016 to provide scientific knowledge on the prevention and treatment of liver cancer. Data from the medical records of liver cancer patients treated in 12 sentinel hospitals in Wuwei city were extracted. SAS and Joinpoint software were used for data analysis, ArcGIS 10.2 software was used to make geographical distribution map, and SaTScan 9.4 software was used for clustering area detection. Of 2271 patients with liver cancer (average age, 58.73 years), 17.7% were 60 to 64 years of age. Majority were males (1680, 74%), with a sex ratio of 2.84. Joinpoint regression analysis from 1995 to 2016 revealed that the standardized liver cancer rate increased [annual average rate of change (AAPC) = 12.80% (95% CI: 9.5%–16.7%)], with a joinpoint in 2009. From 1995 to 2009, the change in overall APC was statistically significant [APC = 16.7 (95% CI: 12.3%–21.3%)]. The average incidence was the highest in Hongshagang Town. After 2005, the incidence gradually increased in each township. Five clusters of liver cancer were noted in Wuwei, including 37 townships. Males had a higher standardized liver cancer rate. After 2009, increase in the incidence of liver cancer was less rapid. The incidence of liver cancer in townships of Wuwei city was non-random, with certain spatial aggregations, covering 37 townships.